The state of renal functions and urokinase activity of urine in newborns and the first month infants with congenital anomalies of the kidney and urinary tract - O. A. Zenchenko; A. V. Suvorova (Бюллетень сибирской медицины)
In our own experience we examined a functional condition of kidneys and urokinase activity of urine at 105 newborns and children of early age with congenital anomalies of the kidney and urinary tract. Inspection was spent at all newborn children after revealing of anomalies of uric system by means of ultrasonic diagnostics. It is established that functional infringements of kidneys at children with congenital anomalies of the kidney and urinary tract have certain sequence: decrease urokinase activity of urine, formation tubular dysfunctions, infringement glomerular functions of kidneys.